"Adding fuel to the fire"? Does exposure to non-consenting adult or to child pornography increase risk of sexual aggression?. (July 2018) - Malamuth, Neil M.
Abstract: This article is the first to integrate the vast research literatures on non-consenting adult and on child pornography (also a form of non-consenting pornography) by using the framework of the Confluence Model of sexual aggression. In contrast to the contradictory conclusions reached by various reviewers and commentators who have typically emphasized a particular methodology or parts of the literature, this review finds a great deal of consistency and convergence among the differing methodologies and literatures that have examined the impact of pornography on individuals. It is concluded that pornography use may add to the risk of sexual aggression only for those men already predisposed to aggress sexually due to more primary causes than pornography use. Highlights: Integrating the vast scientific literature on adult non-consenting pornography and on child pornography. Confluence Model provides a useful framework for integrating the data. Pornography use adds to risk of sexual aggression only for those men already predisposed to aggress sexually.